2010
DOI: 10.1016/j.jcmg.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Myocardial FDG Uptake and the Disease Activity in Cardiac Sarcoidosis

Abstract: Heterogeneous myocardial FDG uptake may be a useful diagnostic marker of disease activity for CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 19 publications
1
84
0
3
Order By: Relevance
“…SUVs are defined as the radioactivity concentration in the region of interest in BqÁmL -1 /(injected dose in BqÁpatient weight in g -1 ). 55 Various metrics for quantification of FDG uptake in cardiac sarcoidosis have been reported, including the maximal SUV values in the heart (SUV max ), 45,55 the total SUV value of the heart, 55 mean SUV of the heart, 56 heart-to-blood pool SUV ratios, 57 coefficient of variance of SUVs, 58 and the volume, 59 and volume-activity 44,59 of voxels with intensities of FDG SUVs above various thresholds. While these methods have not been rigorously compared head-to-head, there is data to suggest that they perform better than visual assessment of normalized images to assess treatment response.…”
Section: F-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%
“…SUVs are defined as the radioactivity concentration in the region of interest in BqÁmL -1 /(injected dose in BqÁpatient weight in g -1 ). 55 Various metrics for quantification of FDG uptake in cardiac sarcoidosis have been reported, including the maximal SUV values in the heart (SUV max ), 45,55 the total SUV value of the heart, 55 mean SUV of the heart, 56 heart-to-blood pool SUV ratios, 57 coefficient of variance of SUVs, 58 and the volume, 59 and volume-activity 44,59 of voxels with intensities of FDG SUVs above various thresholds. While these methods have not been rigorously compared head-to-head, there is data to suggest that they perform better than visual assessment of normalized images to assess treatment response.…”
Section: F-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%
“…Radionuclide scintigraphy using thallium 201, gallium 67, or technetium 99m has shown a wide range of sensitivity, from 18% to 64%, with data suggesting that technetium is the most accurate agent. 6,8,22 Positron emission tomography (PET) scanning is more reliable, with sensitivities between 82% and 100%. However, the reported specificity for PET varies widely, between 39% and 91%.…”
Section: Discussionmentioning
confidence: 99%
“…Takeda show diffusely increased myocardial FDG uptake (7,34). A recent study performed by Yokoyama et al nicely showed that FDG PET/CT with quantification of myocardial SUVmax provides a high sensitivity and specificity for diagnosing CS (16).…”
Section: Patient Monitoring Using Fdg Petmentioning
confidence: 99%